2013
DOI: 10.1007/s00449-013-1076-2
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of culture strategies to enhance capsaicin biosynthesis in suspension and immobilized cell cultures of Capsicum chinense Jacq. cv. Naga King Chili

Abstract: Manipulation of culture strategies was adopted to study the influence of nutrient stress, pH stress and precursor feeding on the biosynthesis of capsaicin in suspension and immobilized cell cultures of C. chinense. Cells cultured in the absence of one of the four nutrients (ammonium and potassium nitrate for nitrate and potassium stress, potassium dihydrogen orthophosphate for phosphorus stress, and sucrose for sugar stress) influenced the accumulation of capsaicin. Among the stress factors studied, nitrate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
1
18
1
1
Order By: Relevance
“…MeJA has been shown to play an important role inducing the accumulation of a wide range of plant secondary metabolites, such as lignin, phytoalexins, flavonoids, pigments, isoprenoids, alkaloids, phenylpropanoids, terpenes [3,38,39,47,48]. A higher level of capsaicinoid production in cell suspension after treatment with MeJA has also been observed [37,40,49].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…MeJA has been shown to play an important role inducing the accumulation of a wide range of plant secondary metabolites, such as lignin, phytoalexins, flavonoids, pigments, isoprenoids, alkaloids, phenylpropanoids, terpenes [3,38,39,47,48]. A higher level of capsaicinoid production in cell suspension after treatment with MeJA has also been observed [37,40,49].…”
Section: Discussionmentioning
confidence: 92%
“…In recent years, numerous studies have demonstrated that both biotic and abiotic elicitors such as Ag + , Co 2+ , β-aminobutyric acid (BABA), methyl jasmonate (MeAJ), and salicylic acid (SA) can stimulate biosynthesis of secondary bioactive components in plants [35][36][37][38][39]. Several studies have confirmed that MeJA can up-regulated the activities of CaPAL and CaCOMT and enhance capsaicin production in cell suspension cultures of Capsicum.…”
Section: Mejamentioning
confidence: 99%
“…Sucrose is a typical osmotic stress agent used for the induction of water stress in plants that also serves as a vital carbon and energy source. The influence of osmotic stress enhanced the accumulation of capsaicin in cell suspension cultures of Capsicum chinensis [42]. It also enhanced the production of steviol glycosides content in both callus as well as suspension culture of Stevia rebaudiana [43].…”
Section: Lightmentioning
confidence: 99%
“…Taxol (plaxitaxol): The bark of the taxus tree (Taxus wallichiana) produces a complex diterpene alkaloid which is a potent anticancer agent because of its unique mode of action on Artemisia annua Artemisinin Callus [66] Artemisia Annua Artemisinin Callus [67] Aspidosperma ramiflorum Ramiflorin Callus [68] Azadirachta indica Azadirachtin Suspension [69] Azadirachta indica Azadirachtin Anther culture [70] Azadirachta indica Azadirachtin Suspension [71] Azadirachta indica Azadirachtin Hairy root [72] Azadirachta indica Azadirachtin Hairy root [73] Brucea javanica Cathin Suspension [74] Bupleurum falcatum Saikosaponins Root [75] Bupleurum chinensis Saikosaponins Root [76] Camellia chinensis Flavones Callus [77] Capsicum annum Capsiacin Callus [78] Capsicum chinense Capsiacin Suspension [79] Capsicum chinense Capsiacin Cotyledon [80] Capsicum chinense Capsiacin Suspension [81] Cassia acutifolia Anthraquinones Suspension [82] Aloe barbadensis Anthraquinone Callus [83] Morinda citrifola Anthraquinone Suspension [84] ( Table 1). Continued.…”
Section: Production Of Bioactive Natural Products Using Tissue Culturmentioning
confidence: 99%
“…Biotransformation of externally fed protocatechuic aldehyde and caffeic acid to capsaicin in freely suspended cells and immobilized cells cultures of C. frutescenshas also been reported [143]. Manipulation of culture strategies were adopted to study the influence of nutrient stress, pH stress and precursor feeding on the biosynthesis of capsaicin in suspension and immobilized cell cultures of C. chinense [80]. Cells cultured in the absence of one of the four nutrients (ammonium and potassium nitrate for nitrate and potassium stress, potassium dihydrogen orthophosphate for phosphorus stress, and sucrose for sugar stress) influenced the accumulation of capsaicin.…”
Section: Gmentioning
confidence: 99%